Peginterferon still has a place in the treatment of hepatitis C caused by genotype 3 virus - Aline Vitali Grando; Paulo Roberto Abrão Ferreira; Mário Guimarães Pessôa; Daniel Ferraz de Campos Mazo; Carlos Eduardo Brandão-Mello; Tânia Reuter; Ana de Lourdes Candolo Martinelli; Mário Peribanez Gonzalez; Ana Catharina Seixas-Santos Nastri; Aléia Faustina Campos; Max Igor Banks Ferreira Lopes; José David Urbaez Brito; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
ABSTRACT Despite recent advances in therapy for chronic hepatitis C (CHC), the disease caused by genotype 3 virus (GEN3) is still considered a treatment challenge in certain patient subgroups. The aim of this retrospective study was to evaluate the effectiveness and safety of the peginterferon (Peg-IFN) and ribavirin (RBV) combination treatment for GEN3/CHC patients, and to evaluate sustained virological response (SVR) indicators and early treatment interruption due to serious adverse events (SAE). This was a retrospective observational study of GEN3/CHC patients, co-infected or not by HIV and treated with Peg-IFN/RBV in nine Brazilian healthcare centers. The study sample included 184 GEN3/CHC patients; 70 (38%) were co-infected with HIV. The overall SVR rate was 57.1% (95% CI 50-64). Among co-infected and mono-infected patients, the SVR rate was 51.4% (36/70) and 60.5% (69/114), respectively (p=0.241). Thirty-four (18.5%) patients experienced SAE and interrupted treatment. SVR was negatively associated with the use of Peg-IFN alpha 2b (PR 0.75; 95% CI 0.58-0.99; p=0.045) and to early treatment interruption due to SAE (PR 0.36; 95% CI 0.20-0.68; p=0.001). Early treatment interruption due to SAE was associated with age (PR 1.06; 95% CI 1.02-1.10; p<0.001) and occurrence of liver cirrhosis (PR 2.06; 95% CI 1.11-3.83; p=0.022). In conclusion, Peg-IFN/RBV might represent an adequate treatment option, mainly in young patients without advanced liver disease or when the use of direct-action drugs is limited to specific patient groups.